Lack of Effects of the Presence of a Dog on Pain Perception in Healthy Participants—A Randomized Controlled Trial - Wagner, Cora; Gaab, Jens; Locher, Cosima; Hediger, Karin (Frontiers in Pain Research, 2021)
Animal-assisted interventions (AAIs) have been shown to be effective in the treatment of pain. Studies suggest that relationships with animals are comparable to relationships with humans and that animals can provide social support. Further, the presence of an animal can strengthen the therapeutic alliance between patients and treatment providers. This suggests that the analgesic effects of AAI might be mediated by social support from an animal or by strengthening the alliance between the patient and the treatment provider. To test these assumptions, we examined the effects of the presence of a dog on pain in a pain assessment and a pain therapy context. 132 healty participants were randomly assigned to the conditions "pain only", "pain + dog", "placebo only", or "placebo + dog". We collected baseline and posttreatment measurements of objective heat-pain tolerance and the objective heat-pain threshold and of the corresponding subjective ratings of heat-pain intensity and unpleasantness as well as of participants’ perceptions of the study conductor. The primary outcome was objective heat-pain tolerance. The presence of the dog did not influence the primary outcome ("pain only" vs "pain + dog": estimate = 0.04, CI = -0.66 – 0.74, p = 0.905; "placebo only" vs "placebo + dog": estimate = 0.43, CI = -0.02 – 0.88, p = 0.059). Participants did also not perceive the study conductor to be more trustworthy in the presence of the dog ("pain only" vs "pain + dog": estimate = 0.10, CI = -0.67 – 0.87, p = 0.796; "placebo only" vs "placebo + dog": estimate = 0.11, CI = -0.43 – 0.64, p = 0.695). The results indicate that the mere presence of a dog does not contribute to pain relief and that the analgesic effects of AAI that previous studies have found is not replicated in our study as AAI did not increase perceived social support and had no effect on the alliance between the patient and the treatment provider. We assume that the animal most likely needs to be an integrated and plausible part of the treatment rationale so that patients are able to form a treatment-response expectation toward AAI.